Andean berry (Vaccinium meridionale Swartz) juice, in combination with Aspirin, displayed antiproliferative and pro-apoptotic mechanisms in vitro while exhibiting protective effects against AOM-induced colorectal cancer in vivo (2022)
ABSTRACT: Colorectal cancer (CRC) can be either prevented or alleviated using conventional drugs combined with natural treatments. Andean berry (AB, Vaccinium meridionale Sw.) is an underutilized berry with promising anti-inflammatory and antiproliferative effects that could be used to alleviate CRC markers in combination with Aspirin, a well-known CRC preventive drug. This research aimed to evaluate the impact of Aspirin, AB juice (ABJ), and their mixture on colorectal cancer in vitro and in vivo. The treatments (ABJ: 0, 10, 20, and 30 % v/v; Aspirin: 0, 10, 15, and 20 mM; and their combination) were assessed on SW480 cells to test their antiproliferative and pro-apoptotic effect. To evaluate their chemopreventive and chemoprotective effect in vivo, azoxymethane (AOM, 15 mg/kg BW) was used as a chemical inductor of early-stage colon cancer. Balb/c mice (8 weeks' age) were randomly assigned to five groups (n = 6 mice/group): control (no treatment), positive control (AOM-treated mice), AOM + Aspirin (20 mM: 25 mg/kg BW), AOM + ABJ (30 % v/v), and AOM + Aspirin + ABJ (Aspirin: 25 mg/kg BW; ABJ: 30 % v/v). ABJ contained phenolic compounds such as 3,4-dihydroxybenzoic and gallic acids, morin, and rutin. The mixture showed a strongest antiproliferative effect than their counterparts (+10.39-46.23 %). Except for Aspirin (20 mM), the cells were not able to proliferate based on the cloning efficiency test. The mixture was the most effective treatment arresting the cell cycle and increasing G2/M cell population (p < 0.01). Aspirin and ABJ showed mainly intrinsic and extrinsic-mediated apoptotic processes, while the mixture decreased most pro-apoptotic (cytochrome C, DR4, DR5, TNFRSF1A, Bax, and Bad) and anti-apoptotic proteins (Hsp70, Hsp32, and XIAP) compared to the untreated cells. In silico simulations highlighted the interaction between rutin and catalase as the strongest affinity (-10.30 Kcal/mol). ABJ and the mixture decreased aberrant crypt foci in vivo compared to AOM-only treated mice and protected the colonic and liver architecture, this was latter used as a secondary indicator of AOM-metabolic activity. The chemopreventive approach was more effective, related to a prior regulation of cancer-protective mechanisms in vivo, alleviating the AOM-induced damage. The results indicated that Aspirin and ABJ mixtures exhibit antiproliferative and pro-apoptotic effects in SW480 cells inducing mechanisms linked to extrinsic (TNF and TRAIL-mediated apoptosis) and intrinsic (Bax and cytochrome C modulation) pathways. At in vivo levels, the treatments displayed defensive effects against the AOM-induced damage as observed by macroscopic measurements. However, more in vitro, and in vivo approaches are required to completely fulfill the pro-apoptotic, anti-proliferative, and chemopreventive/chemoprotective effects of ABJ.